Placental complications among Iraqi Pregnant Women with Placenta Accreta - Nour A. Abdulla; Hawrah Ghafel (Kufa Journal for Nursing Sciences)
Background: Placenta accreta is an abnormal attachment of the placenta to the myometrium. It is the most common reason for an emergency postpartum hysterectomy, which is a major cause of maternal morbidity and mortality. If placenta accreta has been detected or suspected prior to birth, the best time to deliver is about (34-35) weeks, with a multidisciplinary team strategy to prevent complications during birth such as uterine infection, massive vaginal bleeding, uterine wall rupture, and uterine inversion secondary due to tried manual placenta removal.